Collecting and Analysing Data on Climate‐related Local Mobility: the MISTIC Toolkit. Issue 6 (8th June 2016) - Safra de Campos, Ricardo; Bell, Martin; Charles‐Edwards, Elin
Abstract: It is widely recognised that environmental events may trigger permanent and seasonal migration but less attention has been given to the way they shape the everyday mobility that shapes household livelihood strategies. This dearth of attention can be traced to a lack of statistical data, the difficulties of collecting information on local space‐time trajectories and the absence of sound statistical measures by which to express them. We review prior work on the migration–environment nexus and trace the development of methods that aim to capture and measure temporary population movement. We identify nine discrete dimensions of mobility and introduce the Mobility in Space and Time among Individuals and Communities (MISTIC) toolkit that is designed to capture the spatio‐temporal patterns of household everyday mobility using a flexible, participant centred approach that facilitates data recording and subsequent analysis. We illustrate application of the toolkit using data from 90 smallholder, subsistence households in semi‐arid rural Northeast Brazil. The empirical evidence reveals systematic changes in the frequency and duration of both production and consumption‐related movements in response to the 2010–2013 drought. Copyright © 2016 John Wiley & Sons, Ltd.